Knowledge governance for the Anthropocene: Pluralism, populism, and decision‐making. Issue 5 (5th December 2022) - Clement, Sarah
Abstract: Many new models of governance are presented as offering potential to more effectively confront environmental challenges in the Anthropocene by transforming the underlying logic of decision‐making. A common feature of these models is the imperative to integrate multiple forms of knowledge, disciplinary perspectives, and diverse networks of actors both within and outside the academy. These calls for pluralism are not just about it as a democratic principle, but part of improved 'knowledge governance' more equipped to address the multi‐faceted causes and consequences of environmental degradation. Yet the principles behind these improved practices can be lost in translation. While pluralism is elevated as ideal, when decision‐makers are faced with political and social realities of bringing in more voices, the result is often more populist than pluralist, and conflicts difficult to manage. This paper explores how these issues play out by examining co‐production in Australian wildfire governance, revealing concerns about whose knowledge is considered credible and legitimate and how knowledge is used to bolster narratives about both change and the status quo. It also contributes to debates about how populism influences the use of knowledge in policy, and how values influence interpretation and action in relation to new evidence.